HUBUNGAN BEBAN KERJA FISIK DAN MENTAL TERHADAP STRES KERJA PERAWAT DI RSUD DR. H. MOHAMAD RABAIN KABUPATEN MUARA ENIM - Erdius Erdius; Fatwa Sari Tetra Dewi (Berita Kedokteran Masyarakat (BKM), 2017)
Job stress among nurses in Muara Enim: physical and mental workloads analysisPurposeThis study aimed to determine the description of the level of job stress and identify related factors that include workload, job satisfaction and individual characteristics of nurses in hospital of dr. H. Mohamad Rabain Muara Enim. MethodsThis research was a quantitative study with a cross-sectional design. Research subjects were 63 nurses who were selected using proportional stratified random sampling. Independent variables were physical and mental workload. External variables were job satisfaction, gender, age, years of service as employee, and marital status. The dependent variable was job stress. Job stress due to work measurements used a stress scoring questionnaire as the scoring method. Statistical tests were conducted to determine the correlation of job stress with the job stress factors of respondents using chi-square tests on physical workload variable and Fisher's Exact tests for mental workload with Confidence Interval (CI) 95% and p-value < 0.05. ResultsThere was no correlation between physical workload towards job stress in hospital of dr. H. Mohamad Rabain District of Muara Enim (p = 0.69). There was also no correlation between mental workload towards job stress in hospital of dr. H. Mohamad Rabain of Muara Enim district (p = 0.77). ConclusionFactors affecting the physical and mental workload are the absence of percentage between direct, indirect and non-nursing actions, and the differences between young and capable nurses. The work stress experienced by nurses is more influenced by other job factors.